Bacterial and plant natriuretic peptides improve plant defence responses against pathogens. (19th May 2017) - Ficarra, Florencia A.; Grandellis, Carolina; Garavaglia, Betiana S.; Gottig, Natalia; Ottado, Jorgelina
Summary: Plant natriuretic peptides (PNPs) have been implicated in the regulation of ions and water homeostasis, and their participation in the plant immune response has also been proposed. Xanthomonas citri ssp. citri contains a gene encoding a PNP‐like protein ( XacPNP ) which has no homologues in other bacteria. XacPNP mimics its Arabidopsis thaliana homologue AtPNP‐A by modifying host responses to create favourable conditions for pathogen survival. However, the ability of XacPNP to induce plant defence responses has not been investigated. In order to study further the role of XacPNP in vivo, A. thaliana lines over‐expressing XacPNP, lines over‐expressing AtPNP‐A and AtPNP‐A ‐deficient plants were generated. Plants over‐expressing XacPNP or AtPNP‐A showed larger stomatal aperture and were more resistant to saline or oxidative stress than were PNP ‐deficient lines. In order to study further the role of PNP in biotic stress responses, A. thaliana leaves were infiltrated with pure recombinant XacPNP, and showed enhanced expression of genes related to the defence response and a higher resistance to pathogen infections. Moreover, AtPNP‐A expression increased in A. thaliana on Pseudomonas syringae pv. tomato ( Pst ) infection. This evidence led us to analyse the responses of the transgenic plants to pathogens. Plants over‐expressing XacPNP or AtPNP‐A were more resistant to Pst infection than control plants, whereas PNP ‐deficient plants were more susceptible and showed a stronger hypersensitive response when challenged with non‐host bacteria. Therefore, XacPNP, acquired by horizontal gene transfer, is able to mimic PNP functions, even with an increase in plant defence responses.